1984
DOI: 10.1002/art.1780270804
|View full text |Cite
|
Sign up to set email alerts
|

Histopathology of the rheumatoid lesion

Abstract: Histochemical and ultrastructural techniques were used to examine the cartilage-pannus junction of 49 rheumatoid joints. Whereas 24 showed relatively acellular, fibrous pannus tissue, 25 demonstrated "cellular" junctions with different cell types at sites of erosion. Macrophages and fibroblasts were commonly observed as majority cell types in most specimens, but others showed mast cells, polymorphonuclear leukocytes, dendritic, or plasma cells as the predominant cell type. Some showed local accumulations of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 220 publications
(50 citation statements)
references
References 23 publications
2
48
0
Order By: Relevance
“…RA is an inflammatory joint disease associated with pronounced infiltration of various types of inflammatory ceils including mast cells and mononuclear cells (1,2). Various researchers have reported increased levels of cytokines and histamine in RA synovial fluid (8,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RA is an inflammatory joint disease associated with pronounced infiltration of various types of inflammatory ceils including mast cells and mononuclear cells (1,2). Various researchers have reported increased levels of cytokines and histamine in RA synovial fluid (8,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In rheumatoid arthritis (RA), the synovial tissue reveals a proliferation of synovial fibroblasts with an infiltration of various types of inflammatory cells including mast cells and mononuclear cells (1,2). This results in destructive joint changes thought to be driven by a variety of events such as cell secretion, cell-cell interaction, and degradation of the extracellular matrix.…”
Section: Introductionmentioning
confidence: 99%
“…All the metalloproteinases are secreted as precursor forms requiring extracellular activation prior to substrate attack. Activation of the pro- ~-enzymes has been demonstrated in vitro by proteolytic cleavage of their propeptide domains and also by organomercurial compounds such as aminophenyl mercuric acetate (H,NPhHgAc) [2, 4-61, but the activation mechanisms that function in vivo remain unclear.Since mast cells are commonly associated with sites of connective-tissue lysis, for example at sites of tumour invasion in melanoma and breast carcinoma [7, 81 and at cartilage erosion sites in rheumatoid arthritis [9], a potential role for this cell in matrix degradation has been proposed [7, 101. Previous reports showed that mast cell extracts were capable of activating latent collagenase [ l l ] and mast cell tryptase of activating prostromelysin [12].…”
mentioning
confidence: 99%
“…Since mast cells are commonly associated with sites of connective-tissue lysis, for example at sites of tumour invasion in melanoma and breast carcinoma [7, 81 and at cartilage erosion sites in rheumatoid arthritis [9], a potential role for this cell in matrix degradation has been proposed [7, 101. Previous reports showed that mast cell extracts were capable of activating latent collagenase [ l l ] and mast cell tryptase of activating prostromelysin [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation